Phytochemical profiling and fractionation of Helianthemum lippii extract versus silver nanoparticle-modified extract: assessment of photoprotective, anti-hemolytic, antibacterial, and anti-inflammatory properties - Laib, Ibtissam; Boutlilis, Djahra Ali; Alsaeedi, Huda; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
This study examines the photoprotective, anti-hemolytic, antibacterial, and anti-inflammatory properties of silver nanoparticles (Ag NPs) synthesized using Helianthemum lippii extract, compared to various extract fractions: total aqueous extract (AE), flavonoid monoglycosides (FMG), flavonoid diglycosides/triglycosides (FDG/FTG), tannins (TN), and anthocyanins (AC). The HPLC analysis showed that key compounds such as caffeic acid, p-coumaric acid, and gallic acid were identified, contributing to the powerful bioactivities of the AE extract. The physicochemical characterization reveals that the Ag NPs are spherical, with an average size of 35 nm and phytochemicals adsorbed on their surface. For photoprotective properties, the sun protection factor (SPF) was highest for the AC fraction (28.27), followed by TN (27.99), AE (23.20), and Ag NPs (22.50), while FMG displayed a moderate SPF (19.39) compared to the commercial standard Avene® (40.00). For antibacterial activity, the minimum inhibitory concentration (MIC) of Ag NPs was 0.2 mg/mL against Pseudomonas aeruginosa and 0.4 mg/mL against Bacillus subtilis, while AE showed a higher MIC of 2.81 mg/mL against multiple bacterial strains. In anti-inflammatory assays, Ag NPs at 400 µg/mL achieved 79.8% inhibition, outperforming AE (71.75%) and fractions such as FDG/FTG (72.9%) and TN (67.9%), with results comparable to diclofenac (72.63%). Hemolysis assays revealed that AE exhibited the lowest hemolysis rate (1.91% at 25 µg/mL), while Ag NPs induced only 1.35% hemolysis, significantly lower than the sodium dodecyl sulfate (SDS) control (90.48%). These findings highlight the potential of combining natural extracts with phytochemically modified Ag NPs for diverse biomedical applications.